2017
DOI: 10.3390/w9070475
|View full text |Cite
|
Sign up to set email alerts
|

Runoff Responses to Climate and Land Use/Cover Changes under Future Scenarios

Abstract: Climate and land use/cover (LUC) are the two most significant factors that directly affect the runoff process. However, most research on runoff response has focused mainly on projected climate variation, while future LUC variability has been neglected. Therefore, the objective of this study is to examine the impacts of projected climate and LUC changes on runoff. -2020, 2021-2030, 2031-2040 and 2041-2050 period, abbreviated S3). These three scenarios are then input into the Soil and Water Assessment Tool (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…Our results, although refer to specifically developed scenarios, confirm the findings of other studies, which mostly showed a reduction in the groundwater and subsurface flow and an increase of the fast component due to the growth of impervious areas (e.g., Pan et al, ; Zhang et al, ). Sometimes the combination of the two changing factors may smooth the effect of land‐use change (Chawla & Mujumdar, ; Li, Zhang, & Xu, ; Pan et al, ; Pumo, Lo Conti, et al, ); in other cases, the changes in urbanization were demonstrated to have a greater effects (Cuo et al, ; Todd et al, ; Wang & Hejazi, ). Generally, the results depend on the simulated scenarios (either future synthetic scenarios or observed) and region under study (e.g., arid areas, uplands, lowlands).…”
Section: Summary and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results, although refer to specifically developed scenarios, confirm the findings of other studies, which mostly showed a reduction in the groundwater and subsurface flow and an increase of the fast component due to the growth of impervious areas (e.g., Pan et al, ; Zhang et al, ). Sometimes the combination of the two changing factors may smooth the effect of land‐use change (Chawla & Mujumdar, ; Li, Zhang, & Xu, ; Pan et al, ; Pumo, Lo Conti, et al, ); in other cases, the changes in urbanization were demonstrated to have a greater effects (Cuo et al, ; Todd et al, ; Wang & Hejazi, ). Generally, the results depend on the simulated scenarios (either future synthetic scenarios or observed) and region under study (e.g., arid areas, uplands, lowlands).…”
Section: Summary and Discussionsupporting
confidence: 91%
“…Cumulative distribution functions (cdfs) of the hourly annual peak for all the scenarios: The cdf for the reference scenario (BAS-U 0 ) is reported in black, solid curves refer to U 0 map scenarios while dashed curves refer to U 1 map scenarios FIGURE 10 Percentage of variations of the GEV distribution parameters for each scenario with respect to the parameters relative to the reference scenario (BAS-U 0 ), for each of the four rainfall schemes 1, 2, 3, and 4 (along the four axes Our results, although refer to specifically developed scenarios, confirm the findings of other studies, which mostly showed a reduction in the groundwater and subsurface flow and an increase of the fast component due to the growth of impervious areas (e.g., Pan et al, 2017;Zhang et al, 2016). Sometimes the combination of the two changing factors may smooth the effect of land-use change (Chawla & Mujumdar, 2015;Li, Zhang, & Xu, 2014;Pan et al, 2017;Pumo, Lo Conti, et al, 2017); in other cases, the changes in urbanization were demonstrated to have a greater effects (Cuo et al, 2009;Todd et al, 2007;Wang & Hejazi, 2011 (Praskievicz & Chang, 2009). For this reason, the outcomes of this kind of study, including that here presented, should be contextualized in the specific territorial context of application.…”
Section: Figuresupporting
confidence: 86%
See 1 more Smart Citation
“…In the last three decades, many studies have addressed the issue of climate evolution under anthropic pressure [1]. An increase of the annual mean global temperature and changes of other climate parameters have been observed in the last century [2][3][4][5]. In fact, many papers particularly concern global climate modelling and the recent warming due to human activity.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid urbanization enlarges the range of urban area and changes the feature of the ground surface [5]. Land Use/Land Cover (LULC) affect runoff process and impact the climatic condition in urban, especially for the development of UHI [6,7], leading to higher temperatures in the urban areas than the suburban areas. UHI effect, an acknowledged issue in large cities and different climatic regions, is becoming a common concern in smaller cities as well [8].…”
Section: Introductionmentioning
confidence: 99%